TCA cycle signalling and the evolution of eukaryotes. (April 2021) - Ryan, Dylan G; Frezza, Christian; O'Neill, Luke AJ
Abstract : A major question remaining in the field of evolutionary biology is how prokaryotic organisms made the leap to complex eukaryotic life. The prevailing theory depicts the origin of eukaryotic cell complexity as emerging from the symbiosis between an α-proteobacterium, the ancestor of present-day mitochondria, and an archaeal host (endosymbiont theory). A primary contribution of mitochondria to eukaryogenesis has been attributed to the mitochondrial genome, which enabled the successful internalisation of bioenergetic membranes and facilitated remarkable genome expansion. It has also been postulated that a key contribution of the archaeal host during eukaryogenesis was in providing 'archaeal histones' that would enable compaction and regulation of an expanded genome. Yet, how the communication between the host and the symbiont evolved is unclear. Here, we propose an evolutionary concept in which mitochondrial TCA cycle signalling was also a crucial player during eukaryogenesis enabling the dynamic control of an expanded genome via regulation of DNA and histone modifications. Furthermore, we discuss how TCA cycle remodelling is a common evolutionary strategy invoked by eukaryotic organisms to coordinate stress responses and gene expression programmes, with a particular focus on the TCA cycle-derived metabolite itaconate.